2001
DOI: 10.1086/319222
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Acquisition of Levofloxacin-Resistant Streptococcus pneumoniae: A Case-Control Study

Abstract: A case-control study was conducted to identify the risk factors associated with levofloxacin-resistant Streptococcus pneumoniae (LRSP) colonization or infection. Twenty-seven case patients (patients with LRSP) were compared with 54 controls (patients with levofloxacin-susceptible S. pneumoniae). Risk factors that were significantly associated with LRSP colonization or infection, according to univariate analysis, included an older age (median age, 75 years for case patients versus 72.5 years for controls), resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
0
20

Year Published

2003
2003
2008
2008

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(107 citation statements)
references
References 39 publications
4
83
0
20
Order By: Relevance
“…The main concerns relate to increasing resistance of S. pneumoniae to penicillin and, to a lesser extent but also of note, H. influenzae to ampicillin. The association of microbial resistance with treatment failure has been delineated for resistance of S. pneumoniae to penicillin (but only above a minimal inhibitory concentration (MIC) of 2 mg?mL -1 ) [141], macrolides [142,143], and fluoroquinolones (levofloxacin) [144][145][146]. For penicillin resistance levels up to MIC 2 mg?dL -1 , high-dose b-lactams are still an appropriate choice [40,41,147,148].…”
Section: What Classification Should Be Used For Treatment?mentioning
confidence: 99%
“…The main concerns relate to increasing resistance of S. pneumoniae to penicillin and, to a lesser extent but also of note, H. influenzae to ampicillin. The association of microbial resistance with treatment failure has been delineated for resistance of S. pneumoniae to penicillin (but only above a minimal inhibitory concentration (MIC) of 2 mg?mL -1 ) [141], macrolides [142,143], and fluoroquinolones (levofloxacin) [144][145][146]. For penicillin resistance levels up to MIC 2 mg?dL -1 , high-dose b-lactams are still an appropriate choice [40,41,147,148].…”
Section: What Classification Should Be Used For Treatment?mentioning
confidence: 99%
“…9 Although it has been suggested that introduction of moxifloxacin and gatifloxacin, which require both typoisomerase and gyrase production for resistance, will circumvent the growing resistance to fluoroquinolones, there is evidence that resistance to fluoroquinolones is essentially a class ef- fect. 10 Thus, increased use of fluoroquinolones can be anticipated to result in an increase in strains of S pneumoniae that are resistant to all fluoroquinolones. Resistance of P aeruginosa, Pseudomonas mirabilis, E coli, and other common hospital pathogens has increased consistently as fluoroquinolone use has increased.…”
Section: Statement Of Problem Of Resistance To Fluoroquinolonesmentioning
confidence: 99%
“…19 Such uncommon reports of treatment failure with levofloxacin have occurred mostly among predisposed hospitalized patients with chronic respiratory disease. 20 In most countries, levofloxacin resistance among S pneumoniae is Ͻ1%; the minimum inhibitory concentration for 90% of isolates (MIC 90 ) remains at 1 mg/L 17 ; and, provided that optimized regimens are used, fluoroquinolones, including levofloxacin, remain highly effective against this pathogen. Levofloxacin is licensed for the management of drug-resistant S pneumoniae in the United States and has widespread formulary acceptance and guideline inclusion.…”
Section: Microbiologic Considerationsmentioning
confidence: 99%